Optimization and stability of lipid extracts from zooplankton rich side-streams (Calanus finmarchicus) from pelagic processing - Sarra Remadi 1996- (2021)
The majority of marine fishery resources have depleted rapidly in the last 40 years, during which the proportion of fish stocks within biologically sustainable levels has decreased from 90% in 1974, to 65.8% in 2017 (FAO, 2020). As the human population continues to increase, the pressure on wild fish stocks intensifies, and the need for new sustainable resources is becoming a crucial priority. Pelagic fishing by-products and side streams coming out of processing facilities may ease the tension on wild stocks and provide valuable ingredients. Pelagic fish such as Atlantic mackerel (Scomber scombrus) are mainly feeding on zooplankton such as Calanus finmarchicus, and the content of their viscera can be utilized to produce oil. C. finmarchicus has been previously reported to be rich in omega-3 polyunsaturated fatty acids (PUFAs) such as eicosapentaenoic acid (EPA, 20:5 n-3) and docosahexaenoic acid (DHA, 22:6 n-3), as well as in the powerful antioxidant astaxanthin and wax esters. The aim of the present study was to extract oil from a zooplankton rich side stream from pelagic processing using four different extraction methods and comparing the yield of each extraction method. The chemical properties and compositions of the oils and the different phases were also analysed. The highest extraction yield was obtained with heat and enzyme extraction. However, the oil extracted with acetone was richer in polyunsaturated fatty acids (PUFAs) and astaxanthin. The cold extraction method had lower oil yield than the extractions employing heat, while also showing larger shares of PUFAs and astaxanthin. The total lipid content from the different extraction phases were evaluated. The results showed that additional oil can be recovered from the solid and emulsion phases. The solids from the acetone extraction and the emulsion from the heat extraction contained the highest lipid content. Moreover, the different phases showed high concentrations of PUFAs, monounsaturated fatty acids (MUFAs) and astaxanthin. The oxidative status of ...